Personalized additive manufacturing of devices for the management of enteroatmospheric fistulas - Francisco José Calero Castro; Andrés Padillo Eguía; Virginia Durán Muñoz‐Cruzado; Luis Tallón Aguilar; José Tinoco González; Imán Laga; Fernando de laPortilla de Juan; Felipe Pareja Ciuró; Javier Padillo Ruiz (Wiley, 2023)
Abstract Additive manufacturing techniques allow the customized design of medical devices according to the patient's requirements. Enteroatmospheric fistula is a pathology that benefits from this personalization due to its extensive clinical variability since the size and morphology of the wound differ extensively among patients. Standard prosthetics do not achieve proper isolation of the wound, leading to a higher risk of infections. Currently, no effective personalized technique to isolate it has been described. In this work, we present the workflow for the design and manufacture of customized devices adapted to the fistula characteristics as it evolves and changes during the treatment with Negative Pressure Wound Therapy (NPWT). For each case, a device was designed with dimensions and morphology depending on each patient's requirements using white light scanning, CAD design, and additive manufacturing. The design and manufacture of the devices were performed in 230.50 min (184.00-304.75). After the placement of the device, the wound was successfully isolated from the intestinal content for 48-72 h. The therapy was applied for 27.71 ± 13.74 days, and the device was redesigned to adapt to the wound when geometrical evolutionary changes occur during the therapy. It was observed a decrease in weekly cures from 23.63 ± 10.54 to 2.69 ± 0.65 (p = 0.001). The fistulose size was reduced longitudinal and transversally by 3.25 ± 2.56 cm and 6.06 ± 3.14 cm, respectively. The wound depth also decreased by 1.94 ± 1.08 cm. In conclusion, customization through additive manufacturing is feasible and offers promising results in the generation of personalized devices for the treatment of enteroatmospheric fistula.